PENGARUH CORPORATE GOVERNANCE STRUCTURE DAN FINANCIAL DISTRESS TERHADAP LUAS PENGUNGKAPAN SUKARELA - Rachmi Julinda Mulianingsih; Darsono Darsono (Diponegoro Journal of Accounting, 2021)
This study was aimed to examine the effect of corporate governance structure and financial distress on the width of voluntary disclosure. Voluntary disclosure is a disclosure that other than what is required. This disclosure is influenced by various factors, including the seven variables used in this study. The result of this study will show whether the seven variables have an effect on increasing or decreasing voluntary disclosure. This study used the secondary data which was annual reports retrieved from Indonesia Stock Exchange (IDX) website and company’s website. This study used purposive sampling method. 276 companies were selected as samples from 494 companies as the population during 2017-2019. The research method used in this study was multiple linear regression. Agency theory is used in this study to formulated seven hypotheses that lead to the result of the analysis. The result of this study indicated that financial distress had a negative and significant effect on voluntary disclosure. The proportion of audit committee, the audit committee meetings frequency, and competency of audit committee had a positive and significant effect on voluntary disclosure. The result of this study also indicated that board of commissioner independence, board of commissioner meetings frequency, and board of commissioner competency had no effect on voluntary disclosure.